Glucomannan Accumulation Induced by Exogenous Lanthanum in Amorphophallus konjac: Insights from a Comparative Transcriptome Analysis - Xiaoxian Li; Zhouting Zeng; Siyi Zhu; Xirui Yang; Xiaobo Xuan; Zhenming Yu (Biology)
Konjac glucomannan (KGM), derived from Amorphophallus konjac, is increasingly utilized in food and pharmaceutical applications. However, inconsistent KGM production across cultivars jeopardizes its quality and market viability. Lanthanum (La) has been shown to promote KGM levels, but the underlying mechanism remains unclear. In this study, 20~80 mg L−1 La significantly stimulated KGM accumulation compared with the control group. We performed a transcriptome analysis and found 21,047 differentially expressed genes (DEGs), predominantly enriched in carbohydrate and glycan metabolism pathways. A total of 48 DEGs were linked to KGM biosynthesis, with 20 genes (SuSy, INV1/3/5/6, HK1/2, FPK2, GPI3, PGM3, UGP2, GMPP1/4, CslA3~7, CslH2, and MSR1.2) showing significant positive correlations with KGM content. Interestingly, three key terminal pathway genes (UGP1, UGP3, and CslD3) exhibited strong upregulation (log2 fold change > 3). Seven DEGs were validated with qRT-PCR, aligning with the transcriptomic results. Furthermore, 12 hormone-responsive DEGs, including 4 ethylene-related genes (CTR1, EBF1/2, EIN3, and MPK6), 6 auxin-related genes (AUX/IAA1-3, SAUR1-2, and TIR1), and 2 gibberellin-related genes (DELLA1-2), were closely linked to KGM levels. Additionally, the transcription factors bHLH and AP2/ERF showed to be closely related to the biosynthesis of KGM. These results lay the foundation for a model wherein La (Ш) modulates KGM accumulation by coordinately regulating biosynthetic and hormonal pathways via specific transcription factors.